2007
DOI: 10.1016/s0828-282x(07)70783-3
|View full text |Cite
|
Sign up to set email alerts
|

Are there sex-related differences in specialized, multidisciplinary congestive heart failure clinics?

Abstract: C ongestive heart failure (CHF) is the most common cause of hospital admissions in people 65 years of age and older (1). Women represent more than one-half of these CHF hospitalizations (2); thus, it is important to determine whether there are sex-related inequities in the referral and follow-up of CHF patients. A sex-related bias in access to services has been documented in coronary artery disease (3-8) and, to a lesser extent, in CHF (9-12).In the past decade, new developments in treatment have led to improv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 46 publications
2
21
0
Order By: Relevance
“…This observation is supported by the findings that there are more men than women admitted to specialized CHF disease management programs (31,32) and that women tend to be followed more by general practitioners than by specialists (33,34).…”
Section: Discussionmentioning
confidence: 71%
“…This observation is supported by the findings that there are more men than women admitted to specialized CHF disease management programs (31,32) and that women tend to be followed more by general practitioners than by specialists (33,34).…”
Section: Discussionmentioning
confidence: 71%
“…The average age of our sample was considerably higher than what has been reported in other heart failure clinics. 3,15,16 Even so, the patients in our study lived in the community and not in long-term care facilities, making it possible for them to attend the clinic if referred there.…”
Section: Discussionmentioning
confidence: 99%
“…14 However, women make up between 26% and 37% of all patients in these specialized multidisciplinary clinics. 3,15,16 Previous studies suggested that women with preserved systolic function HF consulted specialized HF clinics at a more severe point in time in their disease than their male counterparts 15 and that woman had lower health related quality of life (HRQOL) at admission to the clinic compared to men. 17 Although these results may imply the presence of gender disparity in referral since women had a higher severity of disease at entry to the clinic compared to men, there may be other factors that can account for the gender disparity of referral to HF clinics.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another important area that has not been well explored is whether men and women are equally enrolled in DMPs and whether they derive the same benefits. A recent study has addressed this question and examined the records of 765 patients referred to one of three DMPs in Montreal, Quebec (137). The LVEF and NYHA functional class at entry were similar among men and women with a reduced LVEF.…”
Section: Acute Decompensated Hf During Pregnancymentioning
confidence: 99%